(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
It is established that 11 species of liverworts which belong to 10 genera, 9 families, 6 orders, 2 classes are involved in formation of briocenoses. According to ecological and floristic classification on the basis of Braun and Blanquet’smethod they are presented in the composition of 8 classes, 12 orders, 16 unions, 29 associations and 1 subassociation, 15 unranked groups of moss vegetation. They are Marchantia polymorpha L., Riccia glauca L., Metzgeria furcata (L.) Dumort., Ptilidium pulcherrimum (Weber) Vainio, Lophocolea heterophylla (Schrad.) Dumort., L. minor Nees, Plagiochyla porelloides (Torr. еx Nees) Lindenb., Cephaloziella rubella (Nees) Warnst., Porella platyphylla (L.) Pfeiff., Frullania dilatata (L.) Dumort., Radula complanata (L.) Dumort. Their role in the formation of briocenoses briocoenose is various. Liverworts are presented either as the diagnostic species of syntaxons or as their minor components. The diagnostic species of classes are Lophocolea heterophylla (class Cladonio digitatae-Lepidozietea reptantis Jez. &Vondr. 1962), Metzgeria furcata, Plagiochylla porelloides (Neckeretea complanatae Marst. 1986), Frullania dilatata, Radula complanata (Frullanio dilatatae-Leucodontetea sciuroidis Mohan 1978 em. Marst . 1985). Liverworts Lophocolea heterophylla, Porella platyphylla, Ptilidium pulcherrimum are the diagnostic species of corresponding associations: Lophocoleo heterophyllaе-Dolichothecetum seligeri Phil. 1965, Homalothecio sericei- Porelletum platyphyllae Stǿrm ex Duda 1951, Madotheco platyphyllae-Leskeelletum nervosae (Gams 1927) Barkm. 1958, Ptilidio pulcherrimi-Hypnetum reptile Gapon 2010.The majority of the identified species are the diagnostic species of orders, unions, and subassociations andunranked groups. Only Lophocolea minor, Cephaloziella rubella, Riccia glauca, Plagiochyla porelloides are the minor components of briogroup sand take place in their structure occasionally. The associations where liverworts are diagnostic species have been characterized and the phytocoenotic tables are given for the first time.